Laws of return and ethnic cleansing - Schaeffer, Robert (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
In 1992, the Provisional Government of Eritrea published a Nationality Proclamation that offered citizenship to ethnic nationals who lived abroad in Diaspora communities. This law, like the 'Laws of Return' adopted by other countries (Estonia, Latvia, Lithuania, Israel, and Germany), was designed to encourage immigration, a legitimate purpose. But because this Laws of Return also denied non-national ethnic residents the same rights offered to immigrants, and encouraged the emigration or exit of non-national ethnic residents, it was also discriminatory, which contributed to acrimony and conflict among ethnic groups in Eritrea and also in Ethiopia. When war broke out between Eritrea and Ethiopia in 1998, the Eritrean nationality proclamation was used by governments in both countries to rationalize the unlawful expulsion of non-national ethnic residents, depriving them of their rights and deporting them into involuntary exile. In this context, the law because a weapon of war, a legal instrument of ethnic cleansing for regimes in both Eritrea and Ethiopia. This paper compares laws of return in different countries and examines how they have been used to manage ethnic relations and regulate migration, giving particular attention to the case of Eritrea and Ethiopia.
Keywords: Etiopija; Eritreja; zakonodaja; državljanstvo; imigracija; etnični konflikti; etnično čiščenje